2008
DOI: 10.1055/s-2007-1022538
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of Virchow-Robin Perivascular Spaces: Report of 3 Cases with Different Localizations

Abstract: We report on three different cases with Virchow-Robin spaces, including one with extreme widening causing hydrocephalus. In one patient we have performed neuroendoscopic cyst fenestration to resolve the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Extreme dilations of VRS are rare. Diverse symptoms have been described, depending on their localisation 2 3. Most frequently, radiological signs of hydrocephalus (with various clinical impacts) have been associated with cystic widening of VRS.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme dilations of VRS are rare. Diverse symptoms have been described, depending on their localisation 2 3. Most frequently, radiological signs of hydrocephalus (with various clinical impacts) have been associated with cystic widening of VRS.…”
Section: Introductionmentioning
confidence: 99%
“…Cyst wall biopsy was compatible with enlarged PVSs. Caner also described the case of a patient successfully treated by endoscopic fenestration of the cyst wall [5]. Although this pathology typically occurs in elderly people, Fayeye et al recently reported the case of a 6-year-old boy with "mesencephalic enlarged Virchow-Robin spaces", successfully treated with endoscopic cyst-ventriculostomy [13].…”
Section: Casementioning
confidence: 97%
“…4b), and the patient's signs and symptoms regressed, except for the oculomotor deficit. authors: expanding lacunae [7,9,10], expanding Virchow-Robin spaces [11], benign expanding cerebral cysts [7], giant dilations of perivascular spaces [3,5,12] or enlarged perivascular spaces [4,13], and oddly enough, virchomas [5]. Some of the names clearly recall the possible pathogenesis of these cystic lesions, considered by most authors to be merely an excessive dilation of Virchow-Robin physiological perivascular spaces (PVSs), which can be found anywhere in the brain [14].…”
Section: Casementioning
confidence: 98%
See 2 more Smart Citations